Analysis Of Sea Surface Temperature Trends And Their Relationship With The Indian Ocean Dipole (IOD) In The Southern Waters Of Java During The 2000–2025 Period - Yenni Tri Ayundawati; Zahrani Salsabila; Citra Nur Ilahiyah; Almer Beryl Adifta; Nayadiva Shafinka (International Journal of Health Engineering and Technology, 2026)
Sea Surface Temperature (SST) is a key oceanographic parameter that regulates heat exchange between the atmosphere and the ocean; however, the current trend of global warming threatens thermal stability in tropical regions. This study aims to analyze long-term SST warming trends and identify their response and temporal relationship with the Indian Ocean Dipole (IOD) phenomenon in the southern waters of Java. A quantitative approach was applied using GLORYS12v1 ocean reanalysis data for the period 2000–2025, which were statistically analyzed using the Mann–Kendall test, Sen’s Slope estimator, and lag correlation analysis. The results indicate a highly significant increasing trend in annual SST (Z = 3.791; p = 0.000) with a warming rate of +0.0295°C/year. The highest mean SST occurred during the MAM season (29.17°C), while the lowest was observed during the JJA season (27.16°C). Regarding the IOD phenomenon, the Dipole Mode Index (DMI) and SST anomalies exhibited an inverse relationship with a correlation coefficient of r = −0.47 at a 0-month lag. Positive IOD phases were associated with SST cooling anomalies of up to −0.356°C, whereas negative IOD phases warmed the waters by up to 0.996°C. The consistent warming trend, combined with strong seasonal variability and a relatively weak response to IOD phases, suggests that SST dynamics are not solely controlled by the IOD. The findings demonstrate that the southern waters of Java have experienced significant ocean warming over the last two decades, while IOD variability plays a role in temporally modulating SST changes.